2015
DOI: 10.1380/ejssnt.2015.147
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Zn Doping on the Surface Structure and Initial Growth Processes of InP Thin Film Layers on InP(111)B Substrate

Abstract: The effects of Zn atoms as a dopant on the surface structure and initial growth processes on InP(111)B substrate are theoretically investigated on the basis of surface phase diagrams which are obtained by comparing the adsorption energy given by ab initio calculations with the gas-phase chemical potentials. The calculated surface phase diagrams demonstrate that the Zn-incorporated surface is stabilized under the growth conditions with high Zn supply ratio. Furthermore, In atoms tend to easily adsorb on the Zn-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…In particular, it is important to point out the influence of Zn on γ SV , which has not been considered extensively before. It has already been demonstrated that DEZn can modify the surface of InP substrates, thus affecting γ SV ; , in our case, we expect DEZn to destabilize the catalyst, in particular by increasing its wetting and resulting in a smaller contact angle, by modifying the termination of the (100) InP substrate. There are two contrasting mechanisms expected to act on the catalyst: the first, crucial at high [DEZn], promotes high vertical yield by increasing the catalyst volume and thus the contact angle and affecting the liquid–vapor and liquid–solid interfaces.…”
supporting
confidence: 59%
“…In particular, it is important to point out the influence of Zn on γ SV , which has not been considered extensively before. It has already been demonstrated that DEZn can modify the surface of InP substrates, thus affecting γ SV ; , in our case, we expect DEZn to destabilize the catalyst, in particular by increasing its wetting and resulting in a smaller contact angle, by modifying the termination of the (100) InP substrate. There are two contrasting mechanisms expected to act on the catalyst: the first, crucial at high [DEZn], promotes high vertical yield by increasing the catalyst volume and thus the contact angle and affecting the liquid–vapor and liquid–solid interfaces.…”
supporting
confidence: 59%
“…The PL intensity in this case is influenced mainly by a modification in the density of point defects, such as the introduction of P vacancies [27], which are included because of the increased evaporation of precursors and change in the surface reconstruction of the nanowire top surface, which are both expected with rising temperature [28]. Radiative recombination is then reduced at extremely high temperature by the accumulation of point defects.…”
Section: η Plmentioning
confidence: 99%
“…Even if it is not incorporated in the bulk of the nanowires, it can still accumulate at the surface of the nanowire lateral facets, where it would heavily increase the surface recombination. A possible explanation for the different incorporation of Zn on the top surface (where the axial growth takes place) and the lateral facets (where no radial growth is observed) is explained by the fact that lateral facets have different crystalline orientations, which result in a dissimilar Zn atom adsorption [28]. The adsorption is not influenced by an increased DEZn molar fraction, as even at the lowest flow there would be an excess of Zn atoms.…”
Section: P-doping For Inp P-type Dopingmentioning
confidence: 99%